Customary land governance dynamics and its implications for shea tenure and ecology in selected peri-urban communities in Ghana - Kuusaana, Elias Danyi (Frontiers in Sustainable Food Systems, 2022)
Introduction The shea ecosystem provides critical ecosystem services. However, rapid peri-urbanization threatens the governance of peri-land and shea tree resources and poses multiple risks to urban and peri-urban households. Yet, studies on tree tenure in Ghana have focused on cocoa though shea possesses similar economic prospects. This study examines the customary land tenure systems in the Wa Municipality and their impacts on land and shea through a governance lens. Methods This study was purely qualitative and relied on data from focus group discussions and in-depth interviews with 64 purposely selected participants. To enable the retelling of the participants' stories, the data was first coded, thematised, and analyzed using NVivo 10 software. Results The results show that land and shea rights have been decoupled in peri-urban areas, and the grant of land for farming or housing is sequestered from the right to access and use shea trees without authorization. In view of this, urban usufructs cut shea trees to communicate their opposition to land transactions. Due to the fluidity of customary tenure, some family heads are redefining usufruct entitlements to land and counterclaiming the land and shea trees. In addition, the lack of incentives for smallholders to plant and manage shea trees inhibits shea governance and sustainability. Discussion This is exacerbated by the widespread tenure insecurity over land and investments in shea trees. Under family land jurisdictions, family heads must involve usufructs in all the processes of land transactions and assign them a clear mandate and entitlements in customary land administration to facilitate efficient land and shea governance.